2001
DOI: 10.1107/s0909049500016496
|View full text |Cite
|
Sign up to set email alerts
|

Probability density of wave function of excited photoelectron: understanding XANES features

Abstract: Interpretation of XANES spectra suffers from a poor intuitive understanding of the relation between spectral features and structural elements of a material. An attempt to alleviate this shortcoming is made by exploring a spatial distribution of probability density of wave functions of photoelectrons excited during the photoabsorption process. One has to add incoherently squares of wave functions which describe participating photoelectron diffraction (PED) processes, weighted by normalized PED cross sections. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…26 The XANES intensity is proportional to the probability of absorption of a photon by a core electron. 38 It is reported that the calculated PDOS of O in final state, which includes the core-hole effect, correlates well with the corresponding O K-edge XANES of α-SiO 2 . 39 The PDOS from the ground state calculation is quite different for the PDOS from the final state.…”
Section: Computational Detailssupporting
confidence: 60%
See 1 more Smart Citation
“…26 The XANES intensity is proportional to the probability of absorption of a photon by a core electron. 38 It is reported that the calculated PDOS of O in final state, which includes the core-hole effect, correlates well with the corresponding O K-edge XANES of α-SiO 2 . 39 The PDOS from the ground state calculation is quite different for the PDOS from the final state.…”
Section: Computational Detailssupporting
confidence: 60%
“…As mentioned in Section 2, the XANES intensity is proportional to the probability of absorption of a photon by a core electron. 38 Here, the XANES spectrum is analyzed by comparing it to the PDOS of Cu with a core-hole. Note that it is difficult to evaluate the transition energy by using the pseudopential method, 52 therefore, the transition energy of our Cu K-edge XANES is referenced to the Fermi level.…”
Section: Theoretical K-edge Xanes Of Cu In Cu-ssz-13mentioning
confidence: 99%
“…45 for the first time and its detailed description can be found in the paper of Š ipr. 31 We recall its essence only briefly here.…”
Section: Photoelectron Probability Densitymentioning
confidence: 99%
“…(18) and the amplitudes β (j) L (L ′′ ) from Eq. (13). The angulark-integration in (C1) could be performed analytically in principle.…”
Section: Appendix C: Technical Details Of Pepd Calculationsmentioning
confidence: 99%